Prevalence of Periodontitis in Pakistan: a Systematic Review - Fahim, Ayesha; Shakeel, Sadia; Shahid, Tayyaba Nayab; Anwar, Hafiz Mujtaba; Raja, Anum Ahmed; Khan, Anusha (Journal of University College of Medicine and Dentistry, 2022)
Background One of fundamental components of general health and wellbeing is oral health. Among various oral diseases, periodontitis affects a large number of populations around the developed and underdeveloped countries of the world. The first step to manage this disease at the community level is to know its prevalence and trend. Therefore, this systematic review was planned to document the prevalence of periodontitis at the national and regional level. Methods Literature was searched using various databases, such as PubMed, Google Scholar, Pak Medi net and Eric. Keywords used were “Prevalence”, “Periodontitis”, “Pakistan” “Prevalence of periodontitis in Pakistan”, “prevalence and/or periodontitis and/or Pakistan”. The research methodology was based on the PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) to extract and later analyze relevant studies. Quality assessment of all the included studies was performed using Joanna Briggs Institute (JBI) critical appraisal checklist. Results Thirty studies that fulfilled the inclusion criteria and reported the prevalence of periodontitis in the Pakistani population were included. A total of 17,757 subjects were included in the systematic review from 30 studies. The prevalence estimate of periodontitis (keeping 95%CI) was 37% from Punjab, 40% from Sindh, 20% from Khyber Pakhtunkhwa and 3% from Baluchistan. Conclusion Based on our collection of data prevalence of periodontitis in Pakistan was found to be high. Therefore, it can be concluded that in Pakistan periodontitis is a serious dental issue that must be sorted out to improve the oral health related quality of life in this demographic part. This paper will serve as a baseline for planning future health policies to address this disease in the country.